Research on Curriculum Practice in Study Tour Bases Based on the "Aesthetic Education + Empathy" Model of Volga Manor - Yingnan Liu; Minfang Wei (Education Research on Study Tours and Practice, 2026)
Addressing the pervasive pain points in contemporary study tours, namely travel without meaningful learning, learning without deep engagement, and the formalistic implementation of aesthetic education, this paper introduces the theories of embodied cognition and value internalization to propose an "Aesthetic Education + Empathy" curriculum model. Taking Harbin Volga Manor as the empirical case study site for study tour research, the findings demonstrate that creating embodied learning contexts such as life empathy, rule-based collaboration, craftsmanship and gratitude can effectively break down the cognitive barriers of traditional aesthetic education. Courses at the manor, including Forest Little Knight and Little Baker, follow the closed-loop logic of sensory perception – emotional resonance – meaning construction, and have successfully facilitated students' internalization of moral and aesthetic values, transitioning from physical space perception to spiritual world cultivation. This study provides a replicable theoretical framework and practical reference for study tour bases aiming to transform into an immersive education paradigm.